1991
DOI: 10.1002/1097-0142(19910315)67:6<1707::aid-cncr2820670638>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and stomach cancer risk among a japanese population

Abstract: Using stored serum samples collected during from 1970 to 1972 and/or 1977 to 1979 from a fixed population in Hiroshima and Nagasaki, Japan, serum ferritin, transferrin, and ceruloplasmin levels were determined immunologically for persons in whom stomach (233 cases) or lung cancer (84 cases) subsequently developed as well as for their controls. An elevated stomach cancer risk was associated with low antecedent serum ferritin levels, with more than a threefold excess among those in the lowest compared with the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 12 publications
4
40
1
1
Order By: Relevance
“…The role of ferritin in cancer is not fully understood. It has been shown that an elevated stomach cancer risk is associated with low serum levels of ferritin, with more than a three-fold excess among those in the lowest compared with the highest quintile [32]. Our findings of a possible protective role of ferritin in RCC are in an agreement with this observation.…”
Section: Discussionsupporting
confidence: 92%
“…The role of ferritin in cancer is not fully understood. It has been shown that an elevated stomach cancer risk is associated with low serum levels of ferritin, with more than a three-fold excess among those in the lowest compared with the highest quintile [32]. Our findings of a possible protective role of ferritin in RCC are in an agreement with this observation.…”
Section: Discussionsupporting
confidence: 92%
“…Iron deficiency in rats accelerates carcinogen-induced gastrointestinal cancer and metastasis (24), and case-control studies in humans have demonstrated an inverse relationship between dietary iron intake and gastric adenocarcinoma (11)(12)(13)25); similar associations between low iron stores and colorectal cancer risk have also been reported (26,27). The current study represents the first to not only investigate the combinatorial effect of iron deficiency and H. pylori virulence determinants, but also to demonstrate a synergistic influence of these elements on the development of gastric cancer.…”
Section: Figurementioning
confidence: 99%
“…Iron deficiency is associated with an increased risk for neoplasms that arise within the gastrointestinal tract (10), including the stomach (11)(12)(13). H. pylori infection contributes to iron deficiency (14), and bacterial eradication results in reversal of this disorder (15).…”
Section: Introductionmentioning
confidence: 99%
“…Additional case-control studies revealed the same link in colon 98 and liver cancer. 99,100 Some studies yielded negative results in gastric 101 and epithelial cancers. 102 The link between increased body iron and cancer was also suggested by the decreased cancer incidence in regular blood donors in Sweden.…”
Section: Association Of Iron Levels With Cancermentioning
confidence: 99%